Dendritic cells in the host response to implanted materials. (February 2017) - Keselowsky, Benjamin G.; Lewis, Jamal S.
Abstract: The role of dendritic cells (DCs) and their targeted manipulation in the body's response to implanted materials is an important and developing area of investigation, and a large component of the emerging field of biomaterials-based immune engineering. The key position of DCs in the immune system, serving to bridge innate and adaptive immunity, is facilitated by rich diversity in type and function and places DCs as a critical mediator to biomaterials of both synthetic and natural origins. This review presents current views regarding DC biology and summarizes recent findings in DC responses to implanted biomaterials. Based on these findings, there is promise that the directed programming of application-specific DC responses to biomaterials can become a reality, enabling and enhancing applications almost as diverse as the larger field of biomaterials itself.